The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1017/s1368980018002434
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence thresholds for wasting, overweight and stunting in children under 5 years

Abstract: ObjectivePrevalence ranges to classify levels of wasting and stunting have been used since the 1990s for global monitoring of malnutrition. Recent developments prompted a re-examination of existing ranges and development of new ones for childhood overweight. The present paper reports from the WHO–UNICEF Technical Expert Advisory Group on Nutrition Monitoring.DesignThresholds were developed in relation tosdof the normative WHO Child Growth Standards. The international definition of ‘normal’ (2sdbelow/above the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
281
1
23

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 277 publications
(308 citation statements)
references
References 11 publications
3
281
1
23
Order By: Relevance
“…Compared to the national estimates for Addis, this study reports a prevalence which is approximately 5% higher [25]. Being overweight/obesity was also high in the study population [44], in particular when compared with the prevalence reported in the Ethiopian Demographic and Health Survey (EDHS) 2016 for Addis Ababa (7%) [25]. The differences in our observed prevalence as compared to the EDHS could be due to the small sample size used in the EDHS for Addis (n ≤ 220), which may not reflect the child population of the city.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…Compared to the national estimates for Addis, this study reports a prevalence which is approximately 5% higher [25]. Being overweight/obesity was also high in the study population [44], in particular when compared with the prevalence reported in the Ethiopian Demographic and Health Survey (EDHS) 2016 for Addis Ababa (7%) [25]. The differences in our observed prevalence as compared to the EDHS could be due to the small sample size used in the EDHS for Addis (n ≤ 220), which may not reflect the child population of the city.…”
Section: Discussioncontrasting
confidence: 53%
“…The co-existence of both under-and over-nutrition was evident among preschoolers in Addis Ababa; being overweight has reached significantly high levels [44], constituting an important public health risk, while poor diet and stunting remain as pressing issues. Limited dietary diversity, child stunting, and being overweight were common features among the pre-school children of Addis Ababa regardless of wealth, maternal education and household food security.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using WHZs allowed modeling of the three categories in the same distribution and thus enabled us to reliably determine the relative proportions for each category using an ordinal approach. Based on WHO and United Nations Children's Fund (UNICEF)-defined thresholds, a moderate level of separate or dual conditions is defined as >5-10%, a high level as >10-15% and a very high level as >15% estimated prevalence 11 . Finally, we have defined DBM in this study as the simultaneous occurrence of >5% estimated prevalence for both wasting and overweight within the same locations in the same year.…”
mentioning
confidence: 99%
“…The prevalence of childhood obesity has sharply increased from 1990 to 2010 in low-and middleincome countries compared to the developed countries (29), which can have undesirable effects on physical, mental, and psychosocial health in adolescents (30)(31)(32). Studies reported that, the prevalence of overweight and obesity in adolescents varies in different parts of Iran (4,19,33).…”
Section: Discussionmentioning
confidence: 99%